Enhanced Bio-Oil Production from Nannochloropsis Algae via Catalytic Liquefaction: Synthesis and Application of Iron-based Magnetically Recoverable Catalysts - Narasiman Nirmala; Jayaseelan Arun; Sivaperumal Sanjay Kumar; Manivannan Jayamani; Kumar Sureshkumar; Ahmed Hussain Jawhari; Sivasubramanian Palanisamy; Syed Kashif Ali; Saleh A Al-Farraj (BioResources)
Magnetically recoverable iron-based catalysts were developed, with the goal of being cost-effective, reusable, and environmentally friendly. The use of iron-based magnetically recoverable catalyst enhances the catalytic process efficiency for the enhanced bio-oil yield and quality compared to non-catalytic and conventional catalytic methods. The present study aimed to evaluate the hydrothermal liquefaction (HTL) of Nannochloropsis sp. in the presence of Fe3O4 nanostructures for enhanced bio-oil production.  The use of a magnetic-supported catalyst that is low-cost, safe, and can be reused many times without requiring a regeneration step (by retrieving it magnetically from the solid material) can serve as a novel strategy to be used at an industrial scale. The maximum bio-oil yield 31.4% was obtained with a Fe3O4 catalyst dosage of 0.3 g at temperatures of 300 °C and biomass to solvent ratio of 100 g/L, respectively. The compositional analysis of the produced bio-oil was performed and showed notable characteristics for biofuel application. The synthesized Fe3O4 catalyst was recyclable for up to five repeated cycles and a fluctuated bio yield was achieved for the last three cycles of procreation capability for HTL of Nannochloropsis sp. Further improvisation in designing the next generation magnetically recoverable catalyst with improved stability, efficiency will pay wave way for cost–effective and scalable bio-oil production systems.